Contribution of integrated catchment and surface water management to livestock water productivity in pastoral production systems - Zziwa, Emmanuel; Mugerwa, S.; Owoyesigire, B.; Mpairwe, D.R. (2012)
Seasonal water fluctuations both in quality and quantity negatively affect livestock production and subsequently reduce livestock-water productivity (LWP) in rainfed pastoral production systems. This study aimed at assessing the effects of improved catchment and surface water management on LWP and to establish whether the effects of integrated catchment and surface water management are additive, synergistic or counteractive. Three pastoral production systems of Uganda (settled, semi - settled and non - settled) were considered under three management interventions (improved catchment management, improved surface water management and integrated catchment and surface water management) taking the base scenario as a control. Beneficial livestock outputs (p = 0.155), depleted water (p = 0.76) and LWP (p = 0.488) were not significantly different across production systems but were higher in settled and least in non - settled production systems. Improving catchment management increased LWP by 180%, 458 % and 142% while improving surface water management increased LWP by 62%, 165% and 60% in settled, semi - settled and non - settled production systems. Integrated catchment and surface water management increased LWP by 353%, 518% and 280% in settled, semi - sett led and non - settled production systems respectively. The effects of practicing integrated catchment and surface water management were hence synergistic and not additive. There exists a great potential for improving LWP in water stressed pastoral productio n systems of Uganda by reducing the amount of water depleted in production of animal products through practicing integrated catchment and surface water management interventions as well as increased utilization of crop residues in livestock feeding .